Productivity and Price Trends in Construction Since 1947 - Dacy, Douglas C. (The Review of Economics and Statistics, 1965)
EITTLE is known about the real output, productivity, and price trends in the construction Nevertheless, there exists an undercurrent of feeling that the performance of this giant industry has lagged considerably behind the American economy as a whole. Economists have tended to shy away from this area of research because the available statistics have been viewed as inappropriate or unreliable. Consequently, the field has been pre-empted, more or less, by the popular press which has propagated a most distinct notion. The industry, in the words of one writer, is noted for its incredible inefficiency (particularly home building). As an explanation of . why new homes cost too much, he stated that . home builders are forced to use wasteful and obsolete techniques and materials, do little or no research [and] are hobbled by a maze of outdated building codes.' To the extent that such an opinion is held within the economics profession it usually can be traced to the Department of Commerce's construction composite cost index.2 Since World War II the composite has risen faster than most other well known price indexes and the implication has been drawn that much of the rise has been due to inefficiency. However, the composite is essentially a simple inputcost index 3 and no inference about productivity can be logically deduced from it. To the knowledge of this writer, only a few economists have published any research on real output, productivity, or prices in construction. Most of these have been interested in construction only incidentally, as one sector to be integrated into the whole. Their estimates relating to construction can be summarized as follows: Schultze found that construction prices rose 53.7 per cent over the decade beginning in 1947.4 For the same period, the composite rose 47.5 per cent. Alterman and Jacobs estimated that the average annual change in real product between 1947 and 1955 was 5.6 per cent and 2.5 per cent came from an increase in real product per man-hour.5 This figure is surprisingly large when contrasted with the popular view. Yet it appears from their work that construction productivity lagged considerably behind the average for the economy and even behind total services. Kendrick deflated value added by an output deflator closely akin to the composite to yield an index of real output and estimated that real output per man-hour rose at an average rate of 3.9 per cent between 1948 and 1953,6 but productivity had not advanced between 1909 and 1948. Haber and Levinson, writing in the early fifties, thought that productivity had been increasing by about 1.5 per cent per year in residential construction and two per cent in industrial and commercial building.7 They attributed this low rate to the . economic characteristics of the industry. The most recent estimate is that of Domar, et al.8